2012
DOI: 10.1016/j.atmosres.2012.03.007
|View full text |Cite
|
Sign up to set email alerts
|

Satellite contributions to the quantitative characterization of biomass burning for climate modeling

Abstract: Characterization of biomass burning from space has been the subject of an extensive body of literature published over the last few decades. Given the importance of this topic, we review how satellite observations contribute toward improving the representation of biomass burning quantitatively in climate and air-quality modeling and assessment. Satellite observations related to biomass burning may be classified into five broad categories: (i) active fire location and energy release, (ii) burned areas and burn s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
67
0
22

Year Published

2013
2013
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 107 publications
(93 citation statements)
references
References 283 publications
(296 reference statements)
2
67
0
22
Order By: Relevance
“…The authors compared modeling results to MOPITT (Measurement of Pollution in the Troposphere) satellite data, but it turned out that the particular emission height impact on the overall bias was not quantifiable. Overall, modeling as well as observational studies (e.g., Diner et al, 2008;Val Martin et al, 2010;Ichoku et al, 2012) indicate that wildfire plume heights are highly variable on the global scale. While Freitas et al (2007), Rio et al (2010) and others demonstrated a reasonable performance for their specific plume height parametrizations in particular case studies; other authors including Val Martin et al (2012) and Goodrick et al (2012) presented results that showed a poor to moderate performance of all these models on the global scale.…”
Section: A Veira Et Al: Impact On Transport Black Carbon Concentramentioning
confidence: 99%
“…The authors compared modeling results to MOPITT (Measurement of Pollution in the Troposphere) satellite data, but it turned out that the particular emission height impact on the overall bias was not quantifiable. Overall, modeling as well as observational studies (e.g., Diner et al, 2008;Val Martin et al, 2010;Ichoku et al, 2012) indicate that wildfire plume heights are highly variable on the global scale. While Freitas et al (2007), Rio et al (2010) and others demonstrated a reasonable performance for their specific plume height parametrizations in particular case studies; other authors including Val Martin et al (2012) and Goodrick et al (2012) presented results that showed a poor to moderate performance of all these models on the global scale.…”
Section: A Veira Et Al: Impact On Transport Black Carbon Concentramentioning
confidence: 99%
“…Kahn et al, 2008). Ichoku et al (2012) provide a recent review of this topic. EO data also provide information on the characteristics of the causal fires themselves, including "active fire" (AF) products that detail the location, timing, and FRP of the landscapescale fires occurring within the EO satellite pixels (Giglio et al, 2003;Giglio and Schroeder, 2014;Peterson et al, 2014;Wooster et al, 2012a;Roberts and Wooster, 2008).…”
Section: Earth Observation Data Used To Support Wildfire Injection Hementioning
confidence: 99%
“…FRP is a fire characteristic that has been shown to relate quite directly to the total heat produced by the combustion process (Freeborn et al, 2008) and also to the rate of fuel consumption (Wooster et al, 2005), trace gas (Freeborn et al, 2008), and aerosol (e.g. Ichoku et al, 2012) emission. Such active fire products are usually derived from thermal wavelength Earth observations (Giglio et al, 2003;Roberts and Wooster, 2008;Wooster et al, 2012a).…”
Section: Earth Observation Data Used To Support Wildfire Injection Hementioning
confidence: 99%
“…A queima de biomassa compreende a combustão de todos os tipos de material orgânico (Ichoku et al, 2012) e representa uma importante fonte de emissão de aerossóis e gases traços para a atmosfera, influenciando, dessa forma, o clima, principalmente em escala regional, além de ser um fator introdutório de mudanças na paisagem local e regional. Desta forma, torna-se importante quantificá-la com o intuito de compreender seus impactos nos diferentes biomas e no clima (Schroeder et al, 2014).…”
Section: Introductionunclassified
“…De acordo com Ichoku et al (2012), entre as principais fontes de erro na estimativa da FRP podese citar o ângulo de visada. Com o aumento do ângulo de visada, o tamanho do pixel aumenta e, ainda, a precisão dos algoritmos de detecção de anomalias termais que originam os produtos de fogo ativo pode ser comprometida.…”
Section: Introductionunclassified